MENGUBAH METODE PENDIDIKAN MORAL KOHLBERG DALAM PEMBELAJARAN - Samsul Susilawati (Fak. Tarbiyah UIN Maliki Malang, 2011)
Use the appropriate method of moral education will be better able to improve students' moral considerations. But in reality, the recognition of the need to use the appropriate method in moral education in Indonesia has not carried out properly. It appears from the practice of moral learning which is widely practiced in Indonesia is the lecture method of Samba that was developed based on value investment approach. This method has a negative interpretation. In contrast to the approach to the cultivation of values, other approaches that are not indoktrinatif the cognitive development approach. The development of this approach among others through the use of moral dilemma discussion method.